Long‐term risk of end‐stage renal diseases with maintenance dialysis among chronic hepatitis C patients after antiviral therapy in Taiwan. Issue 8 (30th March 2021) - Hsieh, Meng‐Hsuan; Bair, Ming‐Jong; Tsai, Pei‐Chien; Tseng, Kuo‐Chih; Lo, Ching‐Chu; Chen, Chi‐Yi; Kuo, Hsing‐Tao; Hung, Chao‐Hung; Lai, Hsueh‐Chou; Peng, Cheng‐Yuan; Wang, Jing‐Houng; Chen, Jyh‐Jou; et al.
Abstract: Background and Aim: Chronic hepatitis C virus (HCV) infection is associated with impaired renal function. The aim of this study is to explore the risk of and factors associated with end‐stage renal diseases (ESRD) under maintenance dialysis among HCV patients after anti‐HCV therapy. Methods: A total of 12 696 HCV‐infected patients with interferon‐based therapy, including 9679 (76.2%) achieving sustained virological response (SVR), were enrolled from 23 hospitals in Taiwan. Results: During a mean follow‐up period of 5.3 years (67 554 person‐years), the annual incidence of 4.1/10 000 person‐years, 4.0/10 000 and 4.7/10 000 person‐years among SVR patients and non‐SVR patients, respectively. History of diabetes and baseline estimated glomerular filtration rate < 60 mL/min/m 2, instead of SVR, were the significant risk factors for developing ESRD with maintenance dialysis after anti‐HCV therapy (adjusted hazard ratio 7.75 and 9.78). Conclusion: Diabetes and baseline impaired renal function were strongly associated with progression to ESRD with maintenance dialysis among chronic HCV‐infected patients after antiviral therapy.